2000
DOI: 10.1007/s00418-004-0708-7
|View full text |Cite
|
Sign up to set email alerts
|

Localization of endothelin receptors in bleomycin-induced pulmonary fibrosis in the rat

Abstract: Pulmonary fibrosis is characterized by excessive extracellular matrix deposition with concomitant loss of gas exchange units, and endothelin-1 (ET-1) has been implicated in its pathogenesis. Increased levels of ET-1 from tissues and bronchoalveolar lavage have been reported in patients with pulmonary fibrosis and in animal models after intratracheal bleomycin. We characterized the cellular distribution of alveolar ET receptors by immunohistochemistry in bleomycin-induced pulmonary fibrosis in the rat and deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 40 publications
2
14
0
3
Order By: Relevance
“…For the ET B receptor antibody, we obtained bands of z34, 52, and 60 kDa. In a previous study we used the same antibody in rat lungs and obtained bands of z52 and 34 kDa (Wendel et al 2004) in accordance with the report by Kozuka et al (1991). In the present study we observed an additional band of z60 kDa.…”
Section: Discussionsupporting
confidence: 65%
“…For the ET B receptor antibody, we obtained bands of z34, 52, and 60 kDa. In a previous study we used the same antibody in rat lungs and obtained bands of z52 and 34 kDa (Wendel et al 2004) in accordance with the report by Kozuka et al (1991). In the present study we observed an additional band of z60 kDa.…”
Section: Discussionsupporting
confidence: 65%
“…Both cytokines have been shown to modulate pulmonary fibrosis in murine models, and both have been shown to be highly expressed in the lungs of patients with pulmonary fibrosis (4,(25)(26)(27)(28)(29). Moreover, both of these mediators induce fibroblast differentiation, ECM synthesis, and collagen gel contraction (7,10).…”
Section: Discussionmentioning
confidence: 99%
“…Previous results evaluating ET-A receptor and ET-B receptor expression in AEC have been variable. Wendel and colleagues were unable to detect ET-A or ET-B mRNA expression in type I or type II AEC in rat lung after bleomycin injury (40). In contrast, ET-A receptor expression has been demonstrated in an immortalized AEC line (32) and in the alveolar epithelium of normal and scleroderma lung tissue by immunohistochemistry (41).…”
Section: Discussionmentioning
confidence: 99%